Low levels of detectable pertussis antibody among a large cohort of pregnant women in Canada. Issue 41 (1st October 2018) - Brooks, James I.; Bell, Christopher A.; Rotondo, Jenny; Gilbert, Nicolas L.; Tunis, Matthew; Ward, Brian J.; Desai, Shalini
Abstract: Newborns and infants less than 6 months of age continue to be at highest risk of severe outcomes from pertussis infection. Pertussis vaccination during the last trimester of pregnancy can confer protection to newborns as a result of trans-placental transfer of pertussis antibodies. In several countries, pertussis vaccination in pregnancy is recommended routinely and Canada's National Advisory Committee on Immunization issued similar routine recommendations in February 2018. Using second trimester biobanked plasma samples (n = 1752) collected between 2008 and 2011, we measured the pre-existing anti-pertussis toxin (PT) levels in a large cohort of second-trimester pregnant women using a commercial ELISA test. We found that 97.5% of these women had anti-PT IgG titres below 35 IU/mL. Women with higher incomes had slightly higher anti-PT levels but 96% still had titres <35 IU/ml. In conclusion, almost all of the pregnant women in this large cohort had anti-PT levels low enough to suggest susceptibility to pertussis infection in both the mothers and their newborn infants.